Red-emitting rhodamines with hydroxylated, sulfonated, and phosphorylated dye residues and their use in fluorescence nanoscopy - Kolmakov, Kirill; Hell, Stefan (Chemistry - a European journal, 2012)
Fluorescent dyes emitting red light are frequently used in conventional and super-resolution microscopy of biological samples, although the variety of the useful dyes is limited. We describe the synthesis of rhodamine-based fluorescent dyes with absorption and emission maxima in the range of 621-637 and 644-660 nm, respectively and demonstrate their high performance in confocal and stimulated emission depletion (STED) microscopy. New dyes were prepared by means of reliable chemical transformations applied to a rhodamine scaffold with three variable positions. They feature polarity, water solubility, variable net charges, improved stabilities of N-hydroxysuccinimidyl (NHS) esters, as well as large fluorescence quantum yields in dye solutions and antibody conjugates. The photophysical and imaging properties of dyes containing three different polar groups, namely primary phosphate, sulfonic acid (in two different positions), and hydroxyl were compared. A dye with two primary phosphate groups was explored as a valuable alternative to dyes with “classical” sulfonic acid groups. Due to the increased net charge of the phosphorylated dye (q=−4 at pH 8), it demonstrated a far better electrophoretic mobility compared with analogues with two sulfonic acid groups (q=−2). As an example, one fluorescent dye was designed to be especially convenient for practical use. It is characterized by sufficiently high chemical stability of the NHS ester, its simple isolation, handling, and solubility in aqueous buffers, as well as in organic solvents. All these features, accompanied by a zero net charge in conjugates, were accomplished by the introduction of hydrophilic groups of two types: two hydroxyl groups and one sulfonic acid residue.